The Effect of Employment Stress and Growth Mindset on the Happiness of Korean College Students: The Moderated Mediation Model of Grit (Medico Legal Update, 2019)
Background/Objectives: The purpose of this study was to verify the moderated mediation effect of grit onthe mediating effect of growth mindset in the relationship between employment stress and happiness in 364college students in Korea.Method/Statistical Analysis: For statistical analyses, reliability analysis, correlation analysis, and moderatedmediation effect analysis were performed using SPSS Win.21.0 and PROCESS macro for SPSS version 3.2.Findings: The results of the study showed a statistically significant correlation between happiness andgrowth mindset and grit. Employment stress was negatively correlated with happiness, growth mindset,and grit. In addition, the grit of college students moderated the relationship between employment stress andhappiness via the growth mindset.Improvements/Applications: These results will be used as a new model for grit to control the emotionalstress of college students through the growth mindset.